Deciphering genome-wide transcriptomic changes in grapevines heavily infested by spotted lanternflies - Islam, Md Tariqul; Kudla-Williams, Crosley; Kar, Suraj; Londo, Jason P.; Centinari, Michela; Rosa, Cristina (Frontiers in Insect Science, 2022)
The spotted lanternfly, a newly invasive insect in the U.S. that is a great concern for the grapevine industry, produces damage on its host plants through aggressive feeding, using a piercing and sucking method to feed on the phloem of plants. In the eastern US, adult SLF can invade vineyards through fruit ripening until the end of the growing season; however, it is still unclear how prolonged late-season SLF feeding can affect the health of grapevines, as well as the host responses to this extensive damage. Thus, we have performed a comprehensive genome-wide transcriptome analysis in grapevines heavily infested by the spotted lanternfly, as it occurs in Pennsylvania vineyards, and compared it to other relevant transcriptomes in grapes with different degrees to susceptibility to similar pests. Among a variety of plant responses, we highlight here a subset of relevant biological pathways that distinguish or are common to the spotted lanternfly and other phloem feeders in grapevine. The molecular interaction between spotted lanternfly and the vine begins with activation of signal transduction cascades mediated mainly by protein kinase genes. It also induces the expression of transcription factors in the nucleus, of other signaling molecules like phytohormones and secondary metabolites, and their downstream target genes responsible for defense and physiological functions, such as detoxification and photosynthesis. Grapevine responses furthermore include the activation of genes for cell wall strengthening via biosynthesis of major structural components. With this study, we hope to provide the regulatory network to explain effects that the invasive spotted lanternfly has on grapevine health with the goal to improve its susceptibility.